Dakwah Sunan Drajat dalam Perspektif Islam Nusantara di Pesisir Utara Paciran Lamongan - Zaini, Ahmad Afan (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2026)
This research examines Sunan Drajat's da'wah from the perspective of Nusantara Islam, emphasizing its relevance to the Islamic traditions of the fishing community in Paciran, Lamongan. The purpose of the research is to analyze Sunan Drajat's concept of da'wah, understand the characteristics of the Islamic traditions of the Paciran fishing community, and reveal the relevance and internalization of these da'wah values ​​in the socio-religious practices of coastal communities. This research uses a qualitative method with a literature study approach, field observations, and in-depth interviews with religious leaders, fishing figures, and local tradition practitioners. Data analysis was conducted descriptively and analytically using the theoretical framework of Nusantara Islam and contextual da'wah. The results of the research indicate that Sunan Drajat's da'wah (Islamic preaching) is moderate, inclusive, and transformative, implemented through the values ​​of social solidarity, a religious work ethic, concern for the marginalized, and the harmony of religion and local culture. These values ​​persist not only symbolically but are also concretely internalized in fishing traditions such as Petik Laut (sea harvest), slametan (sacrifice), and the practice of mutual cooperation (gotong royong) within coastal communities. The novelty of this research lies in strengthening empirical evidence that the Islamic traditions of coastal communities are a lived manifestation of contextual Islamic da'wah. This enriches the study of da'wah and Islam Nusantara and provides implications for the development of contemporary da'wah strategies in coastal areas and marginalized communities.